2021
DOI: 10.1016/j.stemcr.2021.01.021
|View full text |Cite
|
Sign up to set email alerts
|

Age-Related Changes in the Inflammatory Status of Human Mesenchymal Stem Cells: Implications for Cell Therapy

Abstract: Human mesenchymal stem/stromal cell (hMSC)-based cell therapies are promising for treating a variety of diseases. The unique immunomodulatory properties of hMSCs have extended their therapeutic potential beyond tissue regeneration. However, extensive pre-clinical culture expansion inevitably drives cells toward replicative “aging” and a consequent decline in quality. These “ in vitro -aged” hMSCs resemble biologically aged cells, which have been reported to show senescence signatures, di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
56
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(57 citation statements)
references
References 96 publications
1
56
0
Order By: Relevance
“…Senescent cells have been shown to possess a characteristic secretome, called senescenceassociated secretory phenotype (SASP) [174], characterized by the production of cytokines, chemokines, growth factors, proteases, and reactive oxygen species; these together modify the local and systemic environment. The SASP acts in an autocrine way, reinforcing the arrest of cell growth, while in a paracrine way it induces senescence in neighboring cells, remodels the extracellular matrix, affects the stem cell niches, and stimulates the recruitment and activation of immune cells favoring an inflammatory state [174][175][176]. It has been reported that TA-MSC treatment of healthy donors with 20 ng/mL of TNF-α for 24 h induces SASP with increased expression of IL-6, IL-8, and monocyte chemotactic protein-1 (MCP-1) [172].…”
Section: Alterations In Cell Morphology and Proliferationmentioning
confidence: 99%
“…Senescent cells have been shown to possess a characteristic secretome, called senescenceassociated secretory phenotype (SASP) [174], characterized by the production of cytokines, chemokines, growth factors, proteases, and reactive oxygen species; these together modify the local and systemic environment. The SASP acts in an autocrine way, reinforcing the arrest of cell growth, while in a paracrine way it induces senescence in neighboring cells, remodels the extracellular matrix, affects the stem cell niches, and stimulates the recruitment and activation of immune cells favoring an inflammatory state [174][175][176]. It has been reported that TA-MSC treatment of healthy donors with 20 ng/mL of TNF-α for 24 h induces SASP with increased expression of IL-6, IL-8, and monocyte chemotactic protein-1 (MCP-1) [172].…”
Section: Alterations In Cell Morphology and Proliferationmentioning
confidence: 99%
“…Clinically, osteogenic ability of BMSCs is weakened under some pathophysiological conditions, such as aging, menopause, trauma, and inflammation, all of which can lead to bone defects and osteoporosis [ 2 4 , 33 ]. We found that quercetin treatment induced BMSC proliferation and osteogenic differentiation, suggesting that quercetin can be used for the clinical treatment of osteoporosis and bone defects.…”
Section: Discussionmentioning
confidence: 99%
“…Human bone marrow mesenchymal stem cells (BMSCs) can undergo self-renewal and osteogenic differentiation, and play a vital function for bone formation and remodeling [1]. Some pathophysiological conditions, such as aging, osteoporosis, and some bone defects can inhibit the osteogenic ability of BMSCs [2][3][4]. Therefore, drugs Bian et al BMC Complement Med Ther (2021) 21:243 that can regulate BMSC osteogenic differentiation need to be developed for the management and treatment of these orthopedic diseases.…”
Section: Introductionmentioning
confidence: 99%
“…This initial work in sustained microgravity conditions indicates that such an environment can lead to the identification of novel targets for enhancing the therapeutic benefit of cardiovascular stem cells or progenitor cells (Camberos, V., et al 2021, Camberos, V., et al 2019, Baio, J., et al 2018.  Expansion of mesenchymal stem cells (MSCs) with improved clinical properties: While stem cells hold great potential for use as therapeutic agents, safe and efficient expansion of stem cells is still a major challenge in the field (Zhang, Y., et al 2021). MSCs are emerging as the most common stem cell type utilized within the field of regenerative medicine (Research and Markets, 2021).…”
Section: Cells With Increased Potency and Expansion Capabilitiesmentioning
confidence: 99%